PANDANGAN HIDUP TOKOH PEREMPUAN DALAM NOVEL “MENEBUS IMPIAN” KARYA ABIDAH EL KHALIEQY - Mujib Utomo (EDU-KATA, 2018)
The author tries to discuss the issue of live view of the main character in the novel Dream Redeeming Work Abidah El-Khalieqy. The approach I use in this research is qualitative descriptive. The author uses the approach for this study sought to describe the objective reality of events there. Data collection and analysis techniques used in this study using steps (1) recording, (2) classification, and (3) interpretation. (3) The results showed three of the figures Nur Kemaljati namely: view of life comes from the religious view of life that is the absolute truth; (2) Worldview People Associated with Meaning Success, and (3) view of life on the meaning of love.